The Effect of Laser Irradiation on Reparative Osteogenesis - Yu., М. Iryanov; N., A. Kiryanov (International Journal of Human Anatomy, 2018)
Introduction: The use of non-medicinal facilities for correcting processes in various pathological conditions is one of the most urgent problems of modern medicine. Purpose of the Work: To study the effect of low-intensity infrared laser radiation on reparative bone formation and angiogenesis in bone regeneration which is formed in treatment of fractures under conditions of transosseous osteosynthesis. Material and Methods: A tibia fracture was modeled experimentally in rats in the control and experimental groups. Reposition and fixation of fragments were performed. The fracture zone in the experimental group animals was exposed to the impact of pulsed infrared laser irradiation of low intensity. Animals from the control group underwent the impact simulation. The operated bones were investigated using the methods of X-ray, light and electron microscopy, X-ray electron probe microanalysis. Results: It was established that laser radiation exposure sessions activated fibrillogenesis and angiogenesis, accelerated compacting of newly formed bone tissue and increased its maturity while primary fracture healing occurred. Prolonged capillary dilatation and endothelium-dependent vasodilation, intensive capillarogenesis were noted after sessions of laser therapy in bone regeneration. Endothelial outgrowth was formed in the lumen of the vessels forming capillary buds that propagate along the “mother” vessels (endovascular capillarogenesis). Conclusion: The data obtained revealed a possible mechanism of laser radiation exposure at the level of a whole organism and proved the effectiveness of its application in clinical practice at the early stages of patient rehabilitation under conditions of transosseous osteosynthesis.
Keywords: reparative osteogenesis; angiogenesis; laser irradiation; fracture; transosseous osteosynthesis.